Factors Associated with Duration of Rehabilitation Among Older Adults with Prolonged Hospitalization. Issue 4 (22nd December 2020) - Nguyen, Danh Q.; Ifejika, Nneka L.; Reistetter, Timothy A.; Makam, Anil N.
Abstract : BACKGROUND/OBJECTIVES: Older adults are prone to functional decline during prolonged hospitalization. Although rehabilitation therapy is critical to preserving function, little is known about rehabilitation duration (RD) in this population. We sought to determine the extent of rehabilitation therapy provided to older adults during prolonged hospitalization, and whether this differs by sociodemographic and clinical characteristics. DESIGN: Retrospective cohort. SETTING: Single‐site safety‐net hospital. PARTICIPANTS: Older adults (≥65 years) hospitalized for ≥14 days between 2016 and 2017. MEASUREMENTS: The primary outcome was RD, defined as the average number of minutes of physical and occupational therapy per week. We used a multivariable generalized linear model to assess for differences in RD by sociodemographic and clinical characteristics. For a sub‐cohort of hospitalizations with a baseline mobility assessment, we repeated analyses including mobility limitation as a covariate. RESULTS: Among 1, 031 hospitalizations by 925 unique patients (median age 72, 49% female, 79% non‐white, 40% non‐English speaking), the median RD was 61.3 minutes/week (interquartile range = 16.5–127.3). Covariates associated with lesser RD included black (57.2 fewer minutes/week; 95% confidence interval (CI) = 22.9–91.4) and Hispanic (75.6 fewer minutes/week; 95% CI = 33.8–117.4) race/ethnicity, speaking a language other than English or Spanish (51.7 fewer minutes/week; 95% CI = 21.3–82.0), prolonged mechanical ventilation (30.0 fewer minutes/week; 95% CI = 6.6–53.3), and do‐not‐resuscitate code status (36.0 fewer minutes/week; 95% CI = 17.1–54.8). The inclusion of mobility limitation among the sub‐cohort (n = 350) did not meaningfully change the associations. CONCLUSION: We found large disparities in RD for racial/ethnic and language minorities and clinically vulnerable older adults (mechanical ventilation and do‐not‐resuscitate code status), independent of clinical severity and functional and cognitive impairment. Greater RD for these groups may improve functional outcomes and narrow the disparity gap.